KONSEPSI TRIPRANGAMA UNTUK MENANAMKAN KESADARAN HUKUM DALAM PEMBELAJARAN IPS MELALUI PEDAGOGI REFLEKTIF - Nugroho, Listyanto Aji; Sariyatun, Sariyatun (Jurnal Pendidikan Sejarah Indonesia, 2020)
Abstract:Â Legal awareness is an important value for the nation building. The legal awareness of Indonesian people is indicated below average. Supposed to make advancement, every people of Indonesian should have a high level of legal awareness. Education offers a solution for this problem. By engaging in education, students are expected to enhance their legal awareness. Using reflective pedagogy paradigm, this study assumed that student can be engaged to contemplate themselves, are they law-abiding citizens? Using a concept of ancient Triprangama law, students are persuaded to cultivate legal awareness though social studies education. The aim of this article is to describe the learning concept to promote the legal awareness of student with social studies subject matter that integrated with Triprangama concept with reflective pedagogy approach.